Citizenship-Rights and duties - "Venkataramiah, E S" (Bangalore, 1988)
There are three basic postulates.......which make an ideal citizen (i) a sense of public spirit, meaning by that the desire to sink his own personal ends in the larger ends of his commu nity, the anxiety to subordi nate himself whenever nec essary for the benefit of the society of which he is a member; (ii) that the citizen should have what we re gard a practical common sense, a shrewd eye on the affairs of the world; and (iii) that the citizen must be able to understand and appreci ate what lies at the bottom of the welfare society, that is what are the different elements that go to make up that welfare. A training of a citizen IS not complete unless it includes a prepa ration not only to under stand but to value and promote constituents welfare..
Keywords: Citizenship